Perceptions and attitudes of pharmacy students towards introducing research project-based learning module in a Malaysian public university - Mohamed Elkalmi, Ramadan; Elnaem, Mohamed Hassan Abdelaziz; Mohd Suhaimi, Azyyati; Mohammed Ahmed, Abdulkareem; Fata Nahas, Abdul Rahman; Jamshed, Shazia Qasim (International Pharmaceutical Federation, 2020)
Objectives: To explore pharmacy students’ attitudes, satisfaction, and feedback regarding the introduction of a new project-based learning (PrBL) module in a Bachelor of Pharmacy (B.Pharm.) curriculum in a Malaysian public university. Method: A pre-tested, validated 33-item web-based questionnaire was administered to third-year undergraduate pharmacy students in a Malaysian school of pharmacy (n=102). The grading and assessment tools consisted of a group-based research proposal, final project presentation, and final project report. Descriptive and inferential data analyses were performed using SPSS version 22. A p-value ≤0.05 was considered statistically significant. Results: There was good receptiveness, positive attitude, and satisfaction towards the PrBL module among the study participants. The vast majority of the students (94.1%) believed that the module helped them in learning a topic that they did not know previously and found that it was fun and entertaining to work with friends. Many of students revealed that the PrBL increased their desire to learn and improve their communication skills (76.9%). Also, they agreed that the PrBL module was suitable to prepare them for future practice and problem solving (72.5%). About half of the students (48.0%) expressed their desire for future courses to adopt a PrBL approach. Overall, the majority of students indicated that they were satisfied with the performance of their supervisors (79.4%), and their supervisors made the aims and objectives of the module clear from the outset (65.7%). Conclusion: A new PrBL module was received with good levels of satisfaction, and it is feasible to introduce such modules in other pharmacy programmes in Malaysia. Good PrBL design, a proper educational environment, and well-trained supervisors assisted in the implementation of the module. Feedback from students and preceptors is essential in module enhancement to accommodate their evolving demands and expectations.